2004
DOI: 10.1002/ijc.20558
|View full text |Cite
|
Sign up to set email alerts
|

E5 protein of human papillomavirus type 16 selectively downregulates surface HLA class I

Abstract: Papillomaviruses (PVs) are small DNA tumor viruses that infect the epithelia of humans and animals, causing benign hyperproliferative lesions. In most cases, PV infections are cleared after several months following activation of the host immune system against viral antigen. 1 However, occasionally the lesions do not regress and can progress to cancer. Certain PVs are more commonly associated with malignancy, including the human PV (HPV) types 16 and 18, high-risk viruses for the development of cervical cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(203 citation statements)
references
References 51 publications
9
187
0
7
Order By: Relevance
“…31 It has been shown that HPV 16 E5 has the ability to selectively retain HLA class I A and B complexes in the golgi apparatus, preventing peptide presentation to CTLs. 32 This is consistent with our observation that the variation in class I genes may not determine the efficiency of the immune response. Rather, the observed associations imply that HLA class II antigens act indirectly on the CTL response by activation of T-helper cells.…”
Section: Discussionsupporting
confidence: 92%
“…31 It has been shown that HPV 16 E5 has the ability to selectively retain HLA class I A and B complexes in the golgi apparatus, preventing peptide presentation to CTLs. 32 This is consistent with our observation that the variation in class I genes may not determine the efficiency of the immune response. Rather, the observed associations imply that HLA class II antigens act indirectly on the CTL response by activation of T-helper cells.…”
Section: Discussionsupporting
confidence: 92%
“…Cells were transiently transfected using a pCIneo E5-HA expression vector (Ashrafi et al, 2005) (HaCaT E5) (a) HaCaT cells were transiently transfected using pCI-neo-E5-HA expression vector (HaCaT E5) or using the empty vector alone (HaCaT pCI-neo). After 24 h from transfection, 16E5 expression was assessed by qualitative PCR (left panel, top) and b-actin mRNA was used as internal control: while the 16E5 band is visible only in HaCaT E5 cells, the band corresponding to actin is detected in both RT þ samples.…”
Section: Hpv 16e5 Expression Does Not Affect Kgfr Internalization Butmentioning
confidence: 99%
“…HaCaT cells were transiently transfected or co-transfected with pCI-neo empty vector or pCI-neo containing human KGFR cDNA or with pCI-neo containing 16E5-HA (Ashrafi et al, 2005) using jetPEI DNA Transfection Reagent (Polyplus-transfection, New York, NY, USA) according to the manufacturer's instructions. Transfected cells were collected 24 h after transfection for evaluation of protein expression and internalization assays.…”
Section: Cells and Treatmentsmentioning
confidence: 99%
“…60 Furthermore, the E5 early protein of HPV can also cause retention of MHC class I molecules in the Golgi apparatus, thereby preventing their transport to the cell surface. 61,62 However, the mechanism of MHC class I antigen retention by E5 is not well understood.…”
Section: Retention Of Mhc Class I Molecules In Subcellular Compartmentsmentioning
confidence: 99%